The Date of the City Walls of Jerusalem during the Biblical Period - Ussishkin , David (Antiguo Oriente, 2024)
In a previous paper I summarized my views on the date of the city walls of biblical Jerusalem. I have argued that Jerusalem was surrounded by a city wall for the first time in the late 8th century BCE, only after the Southwest Hill was settled and became part of the city. Beforehand, during the Bronze Age and earlier parts of the Iron Age, Jerusalem was an unfortified settlement. New important discoveries have recently been made in various excavations continuously being carried out in the City of David. The present paper evaluates and summarizes afresh the relevant excavated data. In my view, the newly uncovered data reaffirm the conclusion that Jerusalem was surrounded by a city wall for the first time in the second half of the 8th century BCE. Quite possibly the city wall surrounding Jerusalem of that period was built by Ahaz King of Judah or his son Hezekiah.